Signaling levels mold the RAS mutation tropism of urethane - Siqi Li; Christopher M Counter (eLife, 2021)
RAS genes are commonly mutated in human cancer. Despite many possible mutations, individual cancer types often have a ‘tropism’ towards a specific subset of RAS mutations. As driver mutations, these patterns ostensibly originate from normal cells. High oncogenic RAS activity causes oncogenic stress and different oncogenic mutations can impart different levels of activity, suggesting a relationship between oncoprotein activity and RAS mutation tropism. Here, we show that changing rare codons to common in the murine Kras gene to increase protein expression shifts tumors induced by the carcinogen urethane from arising from canonical Q61 to biochemically less active G12 Kras driver mutations, despite the carcinogen still being biased towards generating Q61 mutations. Conversely, inactivating the tumor suppressor p53 to blunt oncogenic stress partially reversed this effect, restoring Q61 mutations. One interpretation of these findings is that the RAS mutation tropism of urethane arises from selection in normal cells for specific mutations that impart a narrow window of signaling that promotes proliferation without causing oncogenic stress.